CD151 Promotes Cancer Progression in Triple-Negative Breast Cancer by Inducing EMT through the MAPK Signaling Pathway - Lv H; Zhang B; Weng X; Li Y; Deng C; Wang R; Shi L; Yin Y (Breast Cancer: Targets and Therapy, 2025)
Haishu Lv,1 Beibei Zhang,1 Xi Weng,1 Youjia Li,2 Chaoxian Deng,1 Rui Wang,2 Lei Shi,3 Yuanqin Yin1 1Cancer Institute, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning Province, People’s Republic of China; 2Department of Pathology, The Fourth Affiliated Hospital of China Medical University, Shenyang, Liaoning Province, People’s Republic of China; 3Department of Ophthalmology, The Affiliated Shengjing Hospital of China Medical University, Shenyang, Liaoning Province, People’s Republic of ChinaCorrespondence: Lei Shi, The Affiliated Shenjing Hospital of China Medical University, Shenyang, 110004, People’s Republic of China, Email shiny713@126.com Yuanqin Yin, Department of Tumor Biotherapy and Cancer Research, the First Affiliated Hospital of China Medical University, Shenyang, 110001, People’s Republic of China, Email doustar88@126.comBackground: Breast cancer has become one of the most prevalent malignant neoplasms among women, poses a significant threat to public health. As a member of the tetraspanin family of proteins, CD151 is implicated in tumor progression and has been shown to regulate various cellular and molecular mechanisms that drive malignancy. However, the specific functions of CD151 in triple-negative breast cancer (TNBC) remain unclear. In this study, we aimed to investigate the pro-tumorigenic role of CD151 in TNBC by focusing on its interaction with integrin α 3β 1, which often forms a complex with CD151.Methods: Our study first evaluated CD151 expression in clinical samples from TNBC patients and TNBC cell lines by immunohistochemistry and Western blotting analysis. Through RNA interference (RNAi) and constructed overexpressed plasmids, we further validated the impact of CD151 on the migration and invasion of TNBC cells. Then the differentially expressed genes were screened by single-cell RNA sequencing, and these genes were enriched and analyzed. Co-immunoprecipitation studies demonstrated the binding of CD151 with integrin α 3β 1. Western blotting analysis was used to evaluate the expression of proteins related to epithelial-mesenchymal transition (EMT) and Mitogen-activated protein kinase (MAPK) signaling pathway.Results: CD151 is highly expressed in TNBC tissues and cell lines. It enhanced the migration and invasive ability of TNBC cells by promoting EMT. Co-IP demonstrated the binding of CD151 and integrin α 3β 1. In addition, we found that knockdown of either integrin α 3β 1 or CD151 reduced the migration and invasion of TNBC cells in vitro. Western blot analysis revealed that the CD151-integrin α 3β 1 complex could activate the MAPK signaling pathway in TNBC cells, subsequently leading to EMT of these cells.Conclusion: Based on our findings, we propose a novel mechanism by which CD151 mediates tumor progression through the initiation of EMT. This suggests that CD151 could be considered a potential therapeutic target for TNBC.Keywords: CD151, integrin α 3β 1, TNBC, MAPK signaling pathway, EMT